2019
DOI: 10.1109/access.2019.2925680
|View full text |Cite
|
Sign up to set email alerts
|

OAM Mode Selection and Space–Time Coding for Atmospheric Turbulence Mitigation in FSO Communication

Abstract: Orbital angular momentum (OAM) multiplexing has recently received considerable interest in free space optical (FSO) communications. Propagating OAM modes through free space may be subject to atmospheric turbulence (AT) distortions that cause intermodal crosstalk and power disparities between OAM modes. In this paper, we are interested in multiple-input-multiple-output (MIMO) coherent FSO communication systems using the OAM. We propose a selection criterion for the OAM modes to minimize the impact of the AT. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…IV-B. Subsequently there have been several experimental demonstrations using multiple mode bases and/or indices to increase the resilience to turbulence [133][134][135].…”
Section: A Multiplexing Versus Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…IV-B. Subsequently there have been several experimental demonstrations using multiple mode bases and/or indices to increase the resilience to turbulence [133][134][135].…”
Section: A Multiplexing Versus Diversitymentioning
confidence: 99%
“…Space-time block codes (for example Alamouti and Golden codes) have also been shown to be effective, but simple repetition codes (i.e. time diversity) may be more effective [226][227][228]. Repetition codes are a possible solution to dealing with channel memory, although they introduce latency which would be significant in a multi-hop FSO system, for instance.…”
Section: Impact On Optical Signal Processingmentioning
confidence: 99%
“…investigated the impact of space time coding on the performance of OAM MIMO multiplexing scheme in a turbulent free space link and reported that vertical Bell Laboratories layered space-time (V-Blast) and space-time block codes (STBC) can significantly help undo the effect of atmospheric distortions and noise. Amhoud et al suggested the use of the Golden and the Silver space time codes to mitigate the effect of atmospheric turbulence [288].…”
Section: B Atmospheric Turbulence Effects Mitigationmentioning
confidence: 99%
“…Moreover OAM mode selection can also be used to achieve better rates and lower BER [14], [27]. In the absence of channel state information, space-time coding can also be used as an alternative solution to increase the performance [14]. Spatial diversity can be used at both the transmitter and the receiver in the form of a MIMO system [46].…”
Section: Mimo Oam Links With Spatial Diversitymentioning
confidence: 99%